The status of implementation of photovoltaic systems and its influencing factors in European countries. (2nd August 2022) - Raghoebarsing, Amrita; Farkas, Istvan; Atsu, Divine; Boddaert, Simon; Moser, David; Shirazi, Elham; Reinders, Angèle
Abstract: This paper gives an overview of the status of implementation of photovoltaic (PV) systems among 34 member countries involved in the COST Action PEARL PV in the year 2018. Besides this, influencing factors that have an impact on the implementation of PV systems in each country have been assessed. The implementation of PV systems varies in European countries due to differences in solar irradiation and weather conditions, electricity consumption, national economic situation, and governmental approaches to promote PV. For this paper, data sets covering, among others, numbers installed PV systems, and the variables mentioned above, were collected, processed, and synchronized. Subsequently, relations between data were analyzed by geographic mapping and mutual correlations. The 34 countries evaluated produced together 120 TWh of PV electricity in 2018. It was notable that Germany produced the highest amount (45 TWh) and has the highest share (8.4%) of PV in its electricity generation. Weak correlations were found between the different variables and the gross domestic product, annual global irradiation, number of subsidy schemes, cumulative installed capacity, annual electricity generated by PV, the share of RE, and share of PV. Logically, as expected, strong correlations ( R 2 = 0.9) were found between the number of inhabitants and the annual electricity production and consumption. From our analysis, we conclude that four different groups of countries can be identified to categorize the usability of PV. One type covers countries with a significant unused PV potential while local–global irradiation is redundantly available, such as Turkey, Spain, Cyprus, Portugal, and Israel. Abstract : This study gives an overview of the status of implementation of photovoltaic (PV) systems among 34 member countries of COST Action PEARL PV. They cumulatively produced 120 TWh of PV electricity in 2018. Influencing factors that have an impact on the implementation in each country have been assessed. Strong correlations were found between inhabitants and annual electricity production and consumption, while weak correlations were found between gross domestic product, global irradiation, subsidy schemes, cumulative installed capacity, and other variables.